Forecasting supply and demand in nursing professions : impacts of occupational flexibility and employment structure in Germany - Maier, Tobias [Verfasser]; Afentakis, Anja [Verfasser] (My University, 2013)
"To portray the different possible developments in the supply of nursing professionals, we projected the supply of formally trained nurses and the potential supply of persons who are able to work in a nursing profession. This potential supply of nursing professionals was calculated on the basis of empirical information on occupational mobility provided by the German Microcensus 2005 (Labour Force Survey). We also calculated how the supply of full-time equivalents (FTEs) will develop if current employment structures develop in the direction of employment behaviour in nursing professions in eastern and western Germany. We then compared these different supply scenarios with two demand projections ('status quo' and 'compression of morbidity' scenarios) from Germany's Federal Statistical Office." One of the main findings of the analysis is "that additional potential supply could be generated by especially training more young people for a nursing profession as they tend to stay in their initial occupation. Furthermore, the number of FTEs in nursing professions could be increased by promoting more full-time contracts in Western Germany." (Autorenreferat, BIBB-Doku)
Keywords: S 6.4.5.2 Übrige Gesundheitsberufe (außer Ärzte und Apotheker); G 1.2.3.2 Anforderungen & Bedarfe; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; T 3.5 Statistik; Pflegeberuf; Fachkräftebedarf; Erwerbspersonenpotenzial; Prognose; Statistik